Fortgeschrittene Methoden zur Beschreibung der Wirbelschicht-Sprühgranulation - Li, Zhen (KIT Scientific Publishing, 2013)
A multiscale simulation model is developed by combining the CFD Simulation and the population balance equations to describe a transient process of fluidized bed spray granulation. In this model, the CFD simulation generates the particle growth and nucleation rates in consideration of fluid dynamics, drying and multiple interactions, such as drops deposition, dust integration and nucleation between different particles (drops, dust and granules).